The Principal's Strategy In Developing Teacher Professionalism And Graduates' Quality - Anisa Anisa; Eva Iryani; Mulyadi Mulyadi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the strategies of madrasah principals in developing teacher professionalism and improving the quality of graduates at MAN 1 Merangin. The study used a qualitative approach with descriptive methods. The research informants consisted of the madrasah principal, vice-principals, and teachers selected using purposive sampling techniques. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the madrasah principal's strategy is implemented through participatory planning based on deliberation and the results of academic supervision. The strategy is implemented through training, workshops, MGMP (National Teachers' Group Meeting), academic supervision, and ongoing development, which have an impact on improving teacher competency and the quality of graduates. Supporting factors include the madrasah principal's commitment, religious culture, teacher cooperation, and support for educational policies. Inhibiting factors include limited facilities and infrastructure, internet networks, teacher administrative burdens, and the low digital competency of some senior teachers. The study concludes that the madrasah principal's collaborative, participatory, and sustainable strategy plays a significant role in improving teacher professionalism and the quality of madrasah graduates